Bimbingan Teknis Pembuatan Pupuk Organik di Kota Palangkaraya Kalimantan Tengah - Rastono, Adi; Indarwati, Lisa Dwifani; Ridwan, Awaludin (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aimed to enhance the knowledge and skills of local residents in utilizing peatlands and processing cow manure into organic fertilizer. The activity was conducted in Palangkaraya, Central Kalimantan, on November 2–3, 2023, with 25 participants. The method included delivering materials, administering a pretest, and conducting hands-on training on producing solid organic fertilizer from cow manure and liquid organic fertilizer from cow urine. The results showed a significant improvement in participants' understanding of peatland potential, the benefits of organic fertilizer, and waste processing techniques. All participants expressed readiness to apply and further develop these skills, indicating the success of the program in supporting sustainable agriculture.